Music's meaning: A modern musicology for non-musos - Tagg, Philip (New York Mass Media Music Scholar's Press, 2012)
This book provides no potted accounts of composers, artists, genres or of the music industry. It wont help you bluff your way through conversations about jazz, folk, rap, rock, dubstep, classical music or world music. And it never claims the superiority of one type of music over another... Its job is to present, in terms accessible to the average university student, ways of understanding the phenomenon of music as a meaningful system of sonic representation. (from the Preface)I wrote this book for anyone interested in music who wants to understand how it expresses much more than just itself. This work is based on decades of teaching subjects like Popular Music Analysis and Music and the Moving Image to two sorts of student: those learning under a MUSIC AND NOTHING ELSE régime and students from more of an EVERYTHING EXCEPT THE MUSIC background. The musical competence of 'non-musos' has been an important driving force in this attempt to bridge that gap and to open up the SOUNDs of music to those who don't know what subdominants or sawtooth waves are. I've reduced such 'gobbledygook' to an absolute minimum and no note-reading skill is needed.After the theoretical first part, this book is substantially didactic. It explains things like how to denote a musical structure without specialist jargon, how to use intertextual techniques and reception tests, how to describe voice, and how to identify which aspect of the music has which connotations for which reasons, etc. It also provides simple explanations of music's parameters of expression and of how they can be heard to produce meaning. Examples are drawn from a wide variety of musical repertoires.I hope that those who tend to avoid 'the music' in discourse about music will, 'having read the book' (Beatles, 1967), engage with it instead. Since their 'non-muso' competence has certainly influenced my view of what music studies ought to become, I am convinced that my fellow 'musos' will also find food for thought in these pages.If you've been using writings like Introductory Notes to the Semiotics of Music (1997) or Towards a Musical Sign Typology (1991), please be aware that this book entirely replaces those old texts with better explanations, more substantive conceptualisation and more suggestions for practical application. Most of the book consists of ideas and procedures that I've never previously had time to write up in any coherent form. Most of those ideas and procedures derive from teaching experience, but some I've had to develop more or less from scratch in order to sort out some central problems in discourse about music (e.g. the sections on emotion, affect, feeling, mood and metaphor in Chapter 2 and the whole of Chapters 11 and 12 on the two main aspects of musical 'form').